Saving endangered mammals : a field guide to some of the earth's rarest animals - Maynard, Thane (New York : F. Watts, 1992)
Includes basic facts about a number of endangered mammals and gives information on the threats they face and on efforts to save them from extinction.
Includes bibliographical references (p. 56) and index.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
7.5
3-4
Keywords: Endangered species -- Juvenile literature; Rare mammals -- Juvenile literature; Wildlife conservation -- Juvenile literature; Mammals; Rare animals; Wildlife conservation; Mammals; Rare animals; Wildlife conservation